Demand for M2 in an Emerging-Market Economy : An Error-Correction Model for Malaysia - Sriram, Subramanian (IMF Working Papers; Working Paper ;, 1999)
This paper analyses demand for M2 in Malaysia from August 1973 to December 1995 under both the closed- and open-economy framework. Based on the cointegration and weak-exogeneity test results, short-run dynamic error-correction models are specified and estimated. The results indicate that the demand is for real M2. Both the long- and short-run models are well-specified and are fairly stable. The long-run income elasticity is close to one with the opportunity cost variables carrying the expected signs. The external events have some influence on the stability.